Negative electrode material, preparation method thereof and secondary battery
By doping nano-scale metal M in situ into the silicon oxide and carrying out carbon coating treatment, the problem of irreversible reaction of the silicon oxide negative electrode material during the first charge and discharge process is solved, and the energy density and cycle life of the secondary battery are improved.
Patent Information
- Application Number
- CN202311433921.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-31
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-10-31
AI Technical Summary
The existing silicon oxide negative electrode materials react irreversibly during the first charge and discharge process, resulting in lithium loss, reducing the energy density and cycle life of the secondary battery.
Through in-situ doping technology, nano-scale metal M (such as magnesium) is uniformly doped into silicon oxide, forming silicates containing metal M elements, reducing oxygen content, and improving material stability through carbon coating treatment.
The first-effect and cyclic performance of the negative electrode material is improved, the expansion performance is reduced, and the structural stability and safety of the material are enhanced.
Smart Images

Figure CN119920853A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of battery materials, and in particular to a negative electrode material and a preparation method thereof, and a secondary battery. Background Art
[0002] Among many negative electrode materials, silicon oxide negative electrode materials are high-specific capacity negative electrode materials with relatively mature application technology. Compared with graphite negative electrode materials, the specific capacity of silicon oxide negative electrode materials is as high as 2100mAh / g; compared with crystalline silicon negative electrode materials, silicon oxide negative electrode materials overcome the problem of large volume expansion and greatly improve the cycle life of negative electrode materials. However, since the formation process of Li2O and lithium silicate in the first lithium insertion process of silicon oxide materials is irreversible, the lithium loss caused by these irreversible reactions leads to low initial coulomb efficiency. When designing secondary batteries, excessive positive electrode capacity is required to match. On the one hand, this offsets the high specific capacity of the negative electrode and reduces the energy density of the secondary battery; on the other hand, it also increases the positive electrode consumption cost of the secondary battery.
[0003] In order to solve the problem of low initial charge and discharge coulomb efficiency, the oxygen content in silicon oxide can be reduced in advance to reduce the consumption of lithium ions in the positive electrode material by the irreversible phase Li2O generated during the first charge, thereby improving the energy density of the secondary battery. Common methods include adding exogenous reducing metal elements to react with oxygen elements in silicon oxide to reduce and generate nano-silicon, thereby improving the coulomb efficiency of the material. At the same time, the metal oxide or silicate generated by the reduction reaction can act as a buffer matrix to regulate the stress damage caused by volume change of nano-silicon during lithium alloying and dealloying, thereby maintaining structural integrity and improving the long-term cycle performance of the material.
[0004] For example, a method for improving the first-cycle coulomb efficiency of silicon oxide by mixing silicon oxide powder and metal magnesium powder and heating them for solid-phase doping reduction reaction. The physical and chemical properties of magnesium silicate in the negative electrode material prepared by this method are relatively stable, and the stability of the aqueous slurry is good. However, since the magnesium thermal reduction reaction is a diffusion-controlled reaction, the composition of its products is closely related to the diffusion rate of magnesium vapor. When the powders are mixed in a micron-level state, the magnesium vapor generated by heat starts to react from the outside of the silicon oxide particles and gradually diffuses into the inside of the particles. It is easy to cause the formation of byproducts such as magnesium silicide and magnesium oxide and the rapid growth of silicon grains due to local excess magnesium. And because the diffusion rate of magnesium vapor into the solid is generally low, it is difficult for magnesium to be completely and evenly incorporated into the silicon oxide material, and the distribution of magnesium in the reduction product is also relatively uneven.
[0005] For the in-situ gaseous magnesium doping technology, a method of mixing a silicon and silicon dioxide mixture with metal M and then performing vacuum co-evaporation and condensation is also disclosed. The first efficiency of the negative electrode material prepared by this method reaches more than 83%, which greatly improves the effective utilization rate of lithium ions in the positive electrode material of the secondary battery, and its aqueous slurry has good stability. However, since the reaction of the silicon and silicon dioxide mixture used to generate silicon oxide vapor under heating conditions is a solid-solid interface reaction, the amount of silicon oxide vapor generated will also fluctuate greatly as the reaction proceeds. Therefore, during the mixed deposition process of magnesium vapor and silicon oxide vapor, the local magnesium incorporation ratio is uncontrollable, which can easily lead to uneven growth of silicon grains, affecting the cycle life and safety issues of the negative electrode material.
[0006] Obviously, whether it is solid-phase doping or in-situ gaseous doping technology, the negative electrode material prepared has uneven distribution of doping elements or uneven growth of silicon grains, that is, it is difficult to simultaneously meet the uniform distribution of doping elements between a single particle and multiple particles. Based on this, it is urgent to prepare a new negative electrode material to improve its electrochemical performance. Summary of the invention
[0007] The purpose of the present application is to provide a negative electrode material, a preparation method thereof and a secondary battery. Through in-situ doping technology, the doping of nano-scale metal M is achieved to obtain a negative electrode material with uniform distribution of metal M, thereby reducing the oxygen content in the negative electrode material, which is further applied to batteries to improve the first efficiency and cycle performance.
[0008] To achieve the above objectives, the technical solution of this application is as follows:
[0009] In a first aspect, the present application provides a negative electrode material, comprising a silicon-based core and a carbon layer coated on the surface of the silicon-based core, wherein the silicon-based core comprises nano-silicon and a silicate containing a metal M element;
[0010] The negative electrode material is subjected to cross-section and energy spectrum analysis, and the cross-sections of n1 particles are randomly selected for surface scanning analysis to obtain n1 M element content values, and the standard deviation k1 of the n1 M element content values is calculated, where k1≤10; n2 points are randomly selected inside the cross-section of the particle for point scanning analysis to obtain n2 M element content values, and the standard deviation k2 of the n2 M element content values is calculated, where k2≤5, and 0.1<k2 / k1≤1, wherein n1 is a natural number greater than or equal to 5, and n2 is a natural number greater than or equal to 5.
[0011] In combination with the first aspect, in a preferred embodiment of the present application, the negative electrode material satisfies at least one of the following conditions:
[0012] (1) The silicon-based core also includes silicon oxide;
[0013] (2) The pH value of the negative electrode material satisfies 7<pH≤10.5;
[0014] (3) The M element includes at least one metal element from Groups IA, IIA, and IIIA;
[0015] (4) The M element includes at least one of lithium, sodium, potassium, magnesium, calcium and aluminum;
[0016] (5) The true density of the negative electrode material is 2.0 g / cm 3 -2.6g / cm 3 ;
[0017] (6) The specific surface area of the negative electrode material is 2 m 2 / g-10m 2 / g;
[0018] (7) In the negative electrode material, the mass proportion of the M element is 3%-20%, and the mass proportion of the carbon layer is 1%-20%;
[0019] (8) When the silicate containing the metal M element includes MgSiO3, in the XRD spectrum of the negative electrode material, the diffraction peak of MgSiO3 (610) is between 30° and 31°, the diffraction peak of Si (220) is between 45° and 50°, and the ratio of the two diffraction peak intensities α=I Si(220) / I MgSiO3(610) , 0<α<2;
[0020] (9) When the silicate containing the metal M element includes MgSiO3, according to the XRD spectrum of the negative electrode material and the Scherrer formula Kλ=0.9λ / Bcosθ, it is calculated that the average size of the MgSiO3 grains on the (610) crystal plane is ≤30nm.
[0021] Further preferably, the negative electrode material also satisfies at least one of the following conditions:
[0022] (10) The nano-silicon is dispersed in the silicon oxide;
[0023] (11) The nano-silicon or the silicon oxide is surrounded by the silicate containing the metal M element.
[0024] In combination with the first aspect, in a preferred embodiment of the present application, the thickness of the carbon layer is 50nm-500nm.
[0025] In a second aspect, the present application further provides a method for preparing the negative electrode material according to the first aspect, comprising:
[0026] Placing a metal source material and a pre-disproportionated silicon dioxide material at different positions in the same vacuum heating system for heating and evaporation respectively to obtain a metal source gas and silicon dioxide gas;
[0027] Mixing and condensing the silicon dioxide gas and the metal source gas to obtain a core material;
[0028] The core material is subjected to carbon coating treatment to obtain the negative electrode material.
[0029] In combination with the second aspect, in a preferred embodiment of the present application, the preparation method satisfies at least one of the following conditions:
[0030] A. The preparation method of the pre-disproportionated silicon oxide material comprises: pre-disproportionating an amorphous SiO block to obtain silicon oxide containing disproportionated silicon grains <20 nm, and then pulverizing or crushing to obtain the pre-disproportionated silicon oxide powder or particles;
[0031] B. the size of the pre-disproportionated silicon dioxide material is ≤10 cm;
[0032] C. The metal source material includes at least one of a magnesium source material, a lithium source material, a sodium source material, a potassium source material, a calcium source material, and an aluminum source material;
[0033] D. the metal source gas comprises at least one of magnesium vapor, lithium vapor, sodium vapor, potassium vapor, calcium vapor, and aluminum vapor;
[0034] E. The heating evaporation is carried out in a vacuum or inert gas atmosphere;
[0035] F. The temperature at which the pre-disproportionated silicon dioxide material is heated and evaporated is 1000° C.-1500° C.;
[0036] G. The temperature at which the metal source material is heated and evaporated is 600° C.-1350° C.;
[0037] H. The condensation temperature is 500°C-800°C;
[0038] I. The condensation method includes at least one of water cooling and air cooling;
[0039] J. After the condensation, the method further comprises: collecting the precursor material after the condensation, crushing and classifying the precursor material to obtain the core material;
[0040] K. The carbon coating treatment includes gas phase coating, liquid phase coating or solid phase coating.
[0041] Further preferably, the preparation method further satisfies at least one of the following conditions:
[0042] L. The pre-disproportionation treatment is carried out in an inert gas atmosphere, wherein the inert gas comprises at least one of nitrogen, argon and helium;
[0043] M. The temperature of the pre-disproportionation treatment is 1000°C-1200°C;
[0044] N. The holding time of the pre-disproportionation treatment is 3h-10h;
[0045] O. The magnesium source material includes at least one of metal magnesium powder, metal magnesium ingot, metal magnesium particles, a mixture of magnesium oxide and a reducing substance, and a mixture of magnesium salts and a reducing substance.
[0046] P. The pulverizing method includes mechanical pulverizing, ball milling pulverizing or air flow pulverizing;
[0047] Q. The gas phase-coated gas includes a carbon source gas and a carrier gas;
[0048] R. The temperature of the gas phase coating is 700°C-1000°C.
[0049] Furthermore, the preparation method satisfies at least one of the following conditions:
[0050] S. The carbon source gas includes at least one of methane, ethane, propane, butane, ethylene, propylene, and acetylene;
[0051] T. the carrier gas comprises at least one of nitrogen, argon and helium;
[0052] U. The gas phase covering gas also includes hydrogen.
[0053] In combination with the second aspect, in a preferred embodiment of the present application, the silicon dioxide gas and the metal source gas are mixed under a vacuum condition with a vacuum degree of 0-100Pa.
[0054] In a third aspect, the present application further provides a secondary battery, comprising the negative electrode material described in the first aspect or the negative electrode material prepared by the preparation method described in the second aspect.
[0055] Beneficial effects of this application:
[0056] The silicate containing the metal element M in the negative electrode material system of the present application can obtain a distribution of the M element that conforms to certain characteristics through energy spectrum analysis, and the silicate containing the metal element M can effectively separate the nano-silicon domain and the silicon oxide domain, thereby reducing the performance degradation problem of the negative electrode material caused by the aggregation of silicon clusters due to the electrochemical sintering of nano-silicon during the charge and discharge cycle, so that the negative electrode material has both high initial efficiency and excellent cycle performance, and the silicate can serve as a buffer matrix for nano-silicon and silicon oxide during the process of lithium insertion and extraction to buffer the volume change caused by lithium insertion and extraction, so that the negative electrode material has low expansion performance.
[0057] Furthermore, the pH of the negative electrode material of the present invention is within the range of 7<pH≤10.5, which can solve the problem of active silicon and OH in the alkaline solution when preparing the negative electrode material slurry. - The gas generation problem of the reaction between the two, the bubble problem of the electrode coating, and the cycle performance degradation problem caused by the degradation of the alkalinity of the binder. When the silicate containing the metal M element is mainly MgSiO3, the H2SiO3 generated by the hydrolysis of MgSiO3 causes the slurry alkalinity to be relatively weak. When the MgSiO3 content is low and the Mg2SiO4 content is high, a large amount of Mg2SiO4 will hydrolyze to generate H4SiO4, and at the same time produce more OH - , which will make the slurry more alkaline, OH - It will react with the exposed active silicon in the negative electrode material to generate H2, which will affect the safety performance of the battery.
[0058] The preparation method of the negative electrode material of the present application has a simple process and is easy to operate, and can be quickly industrialized. Through the in-situ doping technology, the nano-scale doping of the metal is achieved by mixed deposition of a gaseous metal source and a gaseous silicon oxide, and a negative electrode material with a uniform distribution of metal silicates is obtained. In particular, a pre-disproportionated silicon dioxide material is used in the preparation method, which can continuously and stably generate silicon dioxide vapor, and then after mixing with the stably generated metal source gas, a negative electrode material with uniform distribution of various substances and better performance is obtained, which reduces the problem of unstable evaporation of silicon dioxide due to the interface reaction being affected by the material contact effect when the traditional silicon and silicon dioxide mixture is used as the raw material, and then the problem of uneven doping of various substances in the prepared negative electrode material is reduced.
[0059] The secondary battery of the present application uses the above-mentioned negative electrode material, which has higher first efficiency and excellent charge and discharge cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0060] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0061] Figure 1 XRD spectrum of the negative electrode material prepared in Example 1;
[0062] Figure 2 This is a SEM / EDS scan of a cross section of a particle of the negative electrode material prepared in Example 1;
[0063] Figure 3 This is a high-magnification SEM image of a cross section of a particle of the negative electrode material prepared in Example 1;
[0064] Figure 4 The cycle capacity performance diagram of the secondary batteries prepared in Example 1 and Comparative Example 1;
[0065] Figure 5 The cyclic expansion performance diagram of the secondary batteries prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0066] As used herein:
[0067] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus comprising the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus. The conjunction "consisting of" excludes any unspecified element, step, or component.
[0068] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0069] In these examples, parts and percentages are by mass unless otherwise indicated.
[0070] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0071] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0072] In order to obtain silicon-oxygen negative electrode materials with excellent performance, in the research of the prior art, there are methods that uniformly dope the gaseous lithium generated by the redox reaction of lithium-containing oxides or silicates with reducing agents into silicon powder and silicon micropowder to prepare silicon-based composite negative electrode materials, whose first efficiency can be as high as about 90%, but the silicon grains in the prepared negative electrode materials are large and the cycle performance is poor. There are also methods that put silicon powder, SiO2 powder, magnesium powder and LiCl powder in different cavities in the same vacuum system, heat and sublimate, and obtain a magnesium-lithium co-doped modified precursor after cooling, and then coat it with a conductive layer. The obtained negative electrode material not only has a high first efficiency, but also has the characteristics of high ionic conductivity of lithium silicate and high bonding strength of magnesium silicate, which further improves the cycle life of the material. However, the preparation conditions are harsh, and the expansion of the negative electrode material during charging and discharging is too large. At the same time, there is also a method of preparing silicon-based negative electrode materials by mixing a mixture of silicon and silicon dioxide with metal M and then using vacuum co-evaporation condensation. Although the first efficiency of the material is improved, due to the poor uniformity of steam evaporation mixing, the size of the silicon grains produced is uneven, the electrical performance is poor, and there are certain safety risks.
[0073] The main purpose of this application is to solve the problem of two-phase and multi-phase steam mixing, and to prepare a negative electrode material with metal M elements that meet certain distribution characteristics, so that the negative electrode material has high initial efficiency and excellent cycle performance, as well as low expansion performance.
[0074] In a first aspect, the present application provides a negative electrode material, comprising a silicon-based core and a carbon layer coated on the surface of the silicon-based core. The silicon-based core of the negative electrode material comprises nano-silicon and a silicate containing a metal M element.
[0075] Among them, the negative electrode material was subjected to cross-section and energy spectrum analysis, especially the distribution of the M element in the core was analyzed, and the results were calculated to obtain the k1 value and k2 value.
[0076] Specifically, n1 particles of the negative electrode material are randomly selected for sectioning, and the section of the n1 particles is subjected to surface scanning energy spectrum analysis to obtain n1 M element content values, and the standard deviation k1 of the n1 metal M element content values is calculated, where k1≤10. n2 points are randomly selected inside the section of the particle for point scanning analysis to obtain n2 M element content values, and the standard deviation k2 of the n2 M element content values is calculated, where k2≤5, and the k1 value and the k2 value also satisfy 0.1<k2 / k1≤1, where n1 is a natural number greater than or equal to 5, and n2 is a natural number greater than or equal to 5.
[0077] For negative electrode materials that meet this condition, the metal silicates in their silicon-based core can effectively separate nano-silicon domains and silicon oxide domains, reducing the performance degradation of the negative electrode material caused by the aggregation of silicon clusters.
[0078] In a preferred embodiment of the present application, the pH value of the negative electrode material of the present application satisfies 7<pH≤10.5, for example, it can be 7.5, 8, 8.5, 9, 9.5, 10 or 10.5. More preferably, the pH value satisfies 7<pH≤10.
[0079] It is understandable that if the pH value in the negative electrode material is too high, when the negative electrode material is prepared into a negative electrode slurry, the exposed Si will react with the OH in the slurry. - If the reaction produces H2, there will be problems such as bubbles in the slurry coating, deterioration of the binder performance due to excessive alkalinity, and further deterioration of the cycle performance, the first effect of the battery capacity, and the safety of the battery. The pH value of the negative electrode material of the present application does not exceed 10.5, which greatly reduces the generation of gas and improves the performance of the battery.
[0080] Silicates containing metal elements M can be written as (MO) n ·SiO2, then when the pH of the negative electrode material meets the above range, (MO) n Silicates with a low SiO2 content and a high SiO2 content will be the main silicate phase in the negative electrode material. Taking magnesium silicate as an example, when MgSiO3 (MgO·SiO2) is the main silicate phase in the negative electrode material, the pH value of the negative electrode material will be relatively low. However, if the content of Mg2SiO4 (2MgO·SiO2) is high, Mg2SiO4 will hydrolyze to produce more OH - , which in turn causes a higher pH, and OH -It is easy to react with exposed active Si to generate H2, which causes the initial efficiency of battery capacity to decay, and the generated gas will also cause serious processing problems during battery slurry coating, which may cause battery bulging failure or explosion, thus causing safety risks. Therefore, when 0<m(Mg2SiO4) / m(MgSiO3)≤1, the ability to cause pH value to rise is weak; thus, the pH value range of the negative electrode material can be stably maintained within the range of 7<pH≤10.5, thus reducing the possibility that the exposed Si in the negative electrode material will react with OH in the aqueous slurry due to excessively high pH value. - The reaction produces H2, which leads to problems such as initial capacity decay and processing gas production.
[0081] When the negative electrode material satisfies the above-mentioned ranges of k1 and k2, as well as the range of pH value, the silicate containing the metal element M is evenly distributed in the inner core, and the nano-silicon or silicon oxide is wrapped and isolated, reducing the processing gas production problem caused by the exposure of active silicon and the sintering problem of nano-silicon clusters during the cycle, thereby bringing a more stable material structure and reducing the consumption of active silicon during the cycle.
[0082] In a preferred embodiment of the present application, the silicon-based core of the negative electrode material also includes silicon oxide. More preferably, nano-silicon is dispersed in silicon oxide, and silicate containing metal M element is wrapped around nano-silicon or silicon oxide. Through the multiple protection of silicon oxide and metal silicate, the exposure of active silicon can be further reduced, and the volume expansion rate during the charge and discharge process is reduced.
[0083] Silicon oxide can be represented by the general formula SiO x (0.5≤x≤2). It can be a material formed by silicon particles dispersed in SiO2, or a material having a tetrahedral structural unit, in which the silicon atom is located at the center of the tetrahedral structural unit, and the silicon atom and the oxygen atom are located at the four vertices of the tetrahedral structural unit.
[0084] In a preferred embodiment of the present application, the metal M element includes at least one metal element from Groups IA, IIA, and IIIA.
[0085] In a preferred embodiment of the present application, the M element includes at least one of lithium, sodium, potassium, magnesium, calcium and aluminum, and is more preferably magnesium.
[0086] In a preferred embodiment of the present application, the true density of the negative electrode material is 2.0 g / cm 3 -2.6g / cm 3 , for example, it can be 2.0 g / cm 3 , 2.1g / cm 3 , 2.2g / cm 3 , 2.3g / cm 3, 2.4g / cm 3 , 2.5g / cm 3 or 2.6 g / cm 3 More preferably, the true density is 2.3 g / cm 3 -2.6g / cm 3 .
[0087] The true density of the negative electrode material of the present application is tested by a gas adsorption expansion method.
[0088] In a preferred embodiment of the present application, the specific surface area of the negative electrode material is 2 m 2 / g-10m 2 / g, for example, it can be 2m 2 / g, 4m 2 / g, 6m 2 / g, 8m 2 / g or 10m 2 / g.
[0089] In a preferred embodiment of the present application, the mass percentage of the M element in the negative electrode material is 3%-20%, for example, it can be 3%, 5%, 7%, 10%, 12%, 15%, 18% or 20%.
[0090] In a preferred embodiment of the present application, the mass proportion of the carbon layer on the surface of the negative electrode material is 1%-20%, for example, it can be 1%, 3%, 5%, 8%, 10%, 12%, 15%, 18% or 20%, more preferably 3%-7%.
[0091] In a preferred embodiment of the present application, the thickness of the surface carbon layer is 50 nm-500 nm, for example, it can be 50 nm, 100 nm, 200 nm, 300 nm, 400 nm or 500 nm.
[0092] In a preferred embodiment of the present application, when the silicate containing the metal M element includes MgSiO3, in the XRD spectrum of the negative electrode material, the diffraction peak of MgSiO3 (610) is between 30°-31°, the diffraction peak of Si (220) is between 45°-50°, and the ratio of the two diffraction peak intensities α=I Si(220) / I MgSiO3(610) , 0<α<2.
[0093] In a preferred embodiment of the present application, when the silicate containing the metal element M includes MgSiO3, according to the XRD spectrum of the negative electrode material and the Scherrer formula Kλ=0.9λ / Bcosθ, the average size of the MgSiO3 grains on the (610) crystal plane is calculated to be ≤30nm.
[0094] In a second aspect, the present application further provides a method for preparing the negative electrode material in the first aspect, comprising:
[0095] S1, placing a metal source material and a pre-disproportionated silicon dioxide material at different positions in the same vacuum heating system for heating and evaporation respectively, to obtain a metal source gas and silicon dioxide gas;
[0096] S2, mixing and condensing the silicon dioxide gas and the metal source gas to obtain a core material;
[0097] S3, subjecting the core material to carbon coating treatment to obtain the negative electrode material.
[0098] In combination with the second aspect, in a preferred embodiment of the present application, the method for preparing the pre-disproportionated silicon oxide material in S1 includes: pre-disproportionating the amorphous SiO block to obtain silicon oxide containing disproportionated silicon grains <20 nm, and then pulverizing or crushing to obtain pre-disproportionated silicon oxide powder or particles.
[0099] Further preferably, the pre-disproportionation treatment is carried out in an atmosphere of an inert gas, wherein the inert gas comprises at least one of nitrogen, argon and helium.
[0100] Further preferably, the temperature of the pre-disproportionation treatment is 1000° C.-1200° C., for example, 1000° C., 1050° C., 1100° C., 1150° C. or 1200° C., and the holding time is 3 h-10 h, for example, 3 h, 5 h, 6 h, 8 h or 10 h. More preferably, the pre-disproportionation treatment is kept at a constant temperature of 1000° C. for 10 h.
[0101] It should be noted that the pre-disproportionated silicon oxide material is selected as the silicon oxide source in this application mainly to reduce the instability of SiO evaporation caused by the interface reaction affected by the material contact effect when using traditional silicon and silicon dioxide as raw materials. Among them, the amorphous SiO is homogenized and disproportionated to obtain silicon oxide with disproportionated silicon grains <20nm, realizing a silicon oxide vapor source with Si and SiO2 uniformly dispersed at the nanometer level on a microscopic level, stabilizing the generation rate of silicon oxide vapor during the entire reaction process, and realizing relatively uniform generation, mixing, condensation and deposition of silicon oxide gas and metal M source gas.
[0102] In a preferred embodiment of the present application, the size of the pre-disproportionated silicon monoxide material in S1 is ≤10 cm, for example, it may be 10 μm, 100 μm, 1 mm, 1 cm, 5 cm or 10 cm.
[0103] In a preferred embodiment of the present application, the metal source material in S1 includes at least one of a magnesium source material, a lithium source material, a sodium source material, a potassium source material, a calcium source material, and an aluminum source material, and more preferably a magnesium source material.
[0104] Further preferably, the magnesium source material includes at least one of metal magnesium powder, metal magnesium ingot, metal magnesium granules, a mixture of magnesium oxide and a reducing substance, and a mixture of magnesium salts and a reducing substance.
[0105] In a preferred embodiment of the present application, the metal source gas in S1 includes at least one of magnesium vapor, lithium vapor, sodium vapor, potassium vapor, calcium vapor, and aluminum vapor, and more preferably magnesium vapor.
[0106] In a preferred embodiment of the present application, when the metal source material and the pre-disproportionated silicon dioxide material are heated and evaporated at different positions of the same vacuum heating system, the pre-disproportionated silicon dioxide material can be placed in a first vacuum heating chamber for heating and evaporation to obtain silicon dioxide gas; the metal source material can be placed in a second vacuum heating chamber for heating and evaporation to obtain the metal source gas.
[0107] Specifically, an inert gas is introduced into the first vacuum heating chamber, and the temperature is heated to 1000°C-1500°C to obtain silicon dioxide gas, for example, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C or 1500°C.
[0108] Inert gas is introduced into the second vacuum heating chamber and the temperature is heated to 700°C-1300°C to obtain metal source gas, for example, it can be 700°C, 800°C, 900°C, 1000°C, 1100°C or 1200°C.
[0109] It can be understood that, in the same vacuum heating system, the heating and evaporation temperatures of the metal source material and the pre-disproportionated silicon dioxide material may be the same or different.
[0110] In a preferred embodiment of the present application, the mixing of the two gases in S2 is carried out under a vacuum condition with a vacuum degree of 0-100Pa.
[0111] In a preferred embodiment of the present application, the condensation temperature in S2 is 500°C-900°C, for example, it can be 500°C, 600°C, 700°C, 800°C or 900°C.
[0112] Further preferably, the condensation method includes at least one of water cooling and air cooling.
[0113] Specifically, the condensation deposition chamber is evacuated, and when the vacuum degree reaches below 100 Pa and the temperature of the condensation chamber reaches 500°C-900°C, the gases in the two vacuum heating chambers are introduced into the condensation deposition chamber for mixing, and then the precursor of the mixture of silicon oxide and metal source is collected on the condenser.
[0114] In a preferred embodiment of the present application, after the condensation in S2, the process further includes: collecting the condensed precursor material, and then crushing and grading the precursor material to obtain the core material.
[0115] More preferably, the pulverizing method includes any one of mechanical pulverizing, ball milling pulverizing and air flow pulverizing.
[0116] In a preferred embodiment of the present application, the carbon coating treatment in S3 includes gas phase coating, liquid phase coating or solid phase coating.
[0117] When gas phase coating is used to prepare the surface carbon layer, the gas required for gas phase coating includes a carbon source gas and a carrier gas; the temperature of the gas phase coating is 700°C-1000°C, for example, it can be 700°C, 800°C, 900°C or 1000°C.
[0118] Optionally, the carbon source gas includes at least one of methane, ethane, propane, butane, ethylene, propylene, and acetylene.
[0119] Optionally, the carrier gas includes at least one of nitrogen, argon and helium.
[0120] Further preferably, during the gas phase coating process, in addition to the carbon source gas and the carrier gas, a certain proportion of hydrogen gas may be introduced, mainly for adjusting the structure of the carbon layer.
[0121] In a third aspect, the present application further provides a secondary battery, comprising the negative electrode material described in the first aspect or the negative electrode material prepared by the method for preparing the negative electrode material described in the second aspect.
[0122] More preferably, the secondary battery is a non-aqueous electrolyte rechargeable battery.
[0123] Through in-situ doping technology, in the technical solution of the present application, gaseous magnesium is used as a magnesium source and mixed with gaseous silicon oxide for deposition to achieve nano-scale magnesium doping, thereby obtaining a negative electrode material that meets the distribution characteristics of metal M and the pH range. The negative electrode material is then subjected to heat treatment reduction to reduce the oxygen content in the active substance, and then powderized and carbon-coated to obtain a high-efficiency silicon dioxide negative electrode material.
[0124] In the preparation method of the negative electrode material of the present application, a silicon oxide source is used for pre-disproportionation treatment, wherein Si and SiO xIt is uniformly dispersed at nanoscale everywhere, with silicon grains less than 20nm, reducing the impact of changes in reaction rate caused by changes in contact area of interfacial reactions. Silicon dioxide vapor can be continuously and stably generated, and after mixing with the continuously and stably generated magnesium vapor, the high first-efficiency silicon oxide negative electrode product with uniform distribution and better performance is obtained.
[0125] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0126] Example 1
[0127] The present application provides a negative electrode material, and the preparation method thereof comprises:
[0128] 1) The amorphous SiO block is subjected to a pre-disproportionation treatment at 1200° C. in an argon gas atmosphere for 10 hours, and then subjected to a powdering treatment after cooling to obtain a pre-disproportionated silicon oxide powder containing silicon grains with an average size of 6.0 nm, wherein the volume distribution of the powder is D50=100 μm, and then the powder is placed in a first vacuum heating chamber of a vacuum heating system, argon gas is introduced, and the powder is heated to 1400° C. to obtain silicon oxide gas;
[0129] 2) placing metal magnesium powder in the second vacuum heating chamber of the vacuum heating system, introducing argon gas, and heating to 700° C. to obtain magnesium vapor;
[0130] 3) Evacuate the vacuum heating system to a vacuum degree of 10Pa;
[0131] 4) passing the gas obtained from the first vacuum heating chamber and the gas from the second vacuum heating chamber into a condensation deposition chamber with a vacuum degree of 10 Pa, and collecting the precursor material on a water-cooled substrate with a temperature of 700° C. in the condensation deposition chamber;
[0132] 5) crushing the precursor of step 4) to a volume distribution D50=5.5 μm by mechanical crushing, classification treatment or the like;
[0133] 6) placing the powder material obtained in step 5) in a rotary kiln, heating it to 900° C., introducing methane, hydrogen and carrier gas nitrogen, adjusting the atmosphere ratio to 2:1:3.5, and gas-coating for 8 hours;
[0134] 7) Collecting the coated materials, breaking them up, screening and removing magnetism to obtain a composite negative electrode material containing silicon oxide.
[0135] This embodiment provides a secondary battery, and a specific preparation method includes:
[0136] The negative electrode material prepared in the above embodiment, conductive carbon black, and PAA glue were prepared into a negative electrode slurry in a mass ratio of 75:15:10, coated on copper foil, and dried to form a negative electrode sheet. A metal lithium sheet was used as a counter electrode, and button cells were assembled in a glove box filled with argon.
[0137] The button cell was subjected to a charge and discharge test at a current density of 0.1 C and a charge and discharge interval of 0.01-1.5 V. The test obtained the first reversible specific capacity and first efficiency of the battery.
[0138] This embodiment also provides a secondary battery, and a specific preparation method includes:
[0139] The negative electrode material prepared in the above embodiment: Super-P: KS-6: CMC: SBR = 92: 2: 2: 2: 2 was prepared into a negative electrode slurry, coated on copper foil, and dried to form a negative electrode sheet. A metal lithium sheet was used as a counter electrode and assembled into a button cell in a glove box filled with argon.
[0140] The button battery was charged and discharged at a current density of 1C in the charge and discharge range of 0.01V-1.5V. The volume expansion rate and capacity retention rate of the battery after 50 cycles were obtained. The expansion performance during the cycle was studied using the in-situ expansion rate test method for the elementary soft-pack battery.
[0141] Example 2
[0142] This embodiment provides a negative electrode material, and the preparation method thereof includes:
[0143] 1) The amorphous SiO block is subjected to a pre-disproportionation treatment at 1200° C. in an argon gas atmosphere for 10 hours, and then subjected to a powdering treatment after cooling to obtain a pre-disproportionated silicon oxide powder containing silicon grains with an average size of 6.0 nm, wherein the volume distribution of the powder is D50=100 μm, and then the powder is placed in a first vacuum heating chamber of a vacuum heating system, argon gas is introduced, and the powder is heated to 1300° C. to obtain silicon oxide gas;
[0144] 2) placing metal magnesium powder in the second vacuum heating chamber of the vacuum heating system, introducing argon gas, and heating to 900° C. to obtain magnesium vapor;
[0145] 3) Evacuate the vacuum heating system to a vacuum degree of 5 Pa;
[0146] 4) passing the gas obtained from the first vacuum heating chamber and the gas from the second vacuum heating chamber into a condensation deposition chamber with a vacuum degree of 5 Pa, and collecting the precursor material on a water-cooled substrate with a temperature of 800° C. in the condensation deposition chamber;
[0147] 5) crushing the precursor of step 4) to a volume distribution D50=5.0 μm by mechanical crushing, classification treatment or the like;
[0148] 6) placing the powder material obtained in step 5) in a rotary kiln, heating it to 980° C., introducing methane, hydrogen and carrier gas argon, adjusting the atmosphere ratio to 3:1:3.5, and performing gas phase coating for 10 hours;
[0149] 7) Collecting the coated materials, breaking them up, screening and removing magnetism to obtain a composite negative electrode material containing silicon oxide.
[0150] The preparation and evaluation of the secondary battery provided in this embodiment are the same as those in Embodiment 1.
[0151] Example 3
[0152] This embodiment provides a negative electrode material, and its preparation method is the same as that of embodiment 1, except that:
[0153] In step 2), the metallic calcium powder is placed in a second vacuum heating chamber of the vacuum heating system, argon gas is introduced, and the mixture is heated to 1300° C.;
[0154] The preparation and evaluation of the secondary battery provided in this embodiment are the same as those in Embodiment 1.
[0155] Example 4
[0156] This embodiment provides a negative electrode material, and its preparation method is the same as that of embodiment 1, except that:
[0157] The temperature for the pre-disproportionation treatment in step 1) is 1000° C. and the time is 10 h, and a pre-disproportionated silicon oxide powder with silicon grains of 5.5 nm is obtained.
[0158] The preparation and evaluation of the secondary battery provided in this embodiment are the same as those in Embodiment 1.
[0159] Example 5
[0160] This embodiment provides a negative electrode material, and its preparation method is the same as that of embodiment 1, except that:
[0161] The vacuum degree in step 3) is 50 Pa, and the precursor material is collected on a water-cooled substrate at 900° C. in step 4).
[0162] The preparation and evaluation of the secondary battery provided in this embodiment are the same as those in Embodiment 1.
[0163] Example 6
[0164] This embodiment provides a negative electrode material, and its preparation method is the same as that of embodiment 1, except that:
[0165] The size of the pre-disproportionated silicon monoxide material in step 1) is a block of 5 cm in size.
[0166] The preparation and evaluation of the secondary battery provided in this embodiment are the same as those in Embodiment 1.
[0167] Comparative Example 1
[0168] This comparative example provides a negative electrode material, and its preparation method is the same as that of Example 2, except that:
[0169] In step 1), silicon dioxide powder with a volume distribution of D50=30 μm and silicon powder with a volume distribution of D50=10 μm are directly mixed in a molar ratio of 1:2, placed in the first vacuum heating chamber of the vacuum heating system, introduced with argon gas, and heated to 1400°C; in step 4), the temperature of the water-cooled substrate in the condensation deposition chamber is 850°C; in step 6), only methane and carrier gas nitrogen are introduced, and the atmosphere ratio is adjusted to 3:3.5.
[0170] The preparation and evaluation of the secondary battery provided in this comparative example are the same as those in Example 1.
[0171] Energy spectrum analysis of the Mg element was performed on the negative electrode materials prepared in the above Examples 1-6 and Comparative Example 1, and energy spectrum analysis of the Ca element was performed on the negative electrode material prepared in Example 3, and k1 and k2 values were obtained respectively.
[0172] The specific test method of energy spectrum analysis is: use Hitachi E-3500 ion grinding machine to cut the prepared negative electrode material particles, observe the cross-sectional morphology and structure on Hitachi S-4800 cold field emission scanning electron microscope, and combine with Oxford energy spectrometer in the UK to observe its elemental composition and distribution.
[0173] At the same time, the pH value of the negative electrode materials prepared in Examples 1-6 and Comparative Example 1 was tested: 5.00±0.01 g of powder sample was weighed, added into 45 mL of pure water, stirred and dispersed, ultrasonicated for 5 minutes and then allowed to stand. The upper clear liquid after standing was tested with a Mettler FE20 pH meter to read the pH value.
[0174] True density test: The true density of the negative electrode material was obtained by using an American Micrometer true density meter (AccuPyc II) and a gas adsorption expansion method.
[0175] Specific surface area test: The specific surface area of the material was calculated using an American Micrometer pore analyzer (TriStar II) with nitrogen adsorption and the BET method.
[0176] XRD test: XRD diffractometer was used to characterize the samples with a scanning range of 10°-90° and a scanning step of 0.05°.
[0177] The performance test results of the negative electrode materials prepared in the above Examples 1-6 and Comparative Example 1 are shown in Table 1, and the electrochemical test results of the negative electrode materials prepared in the embodiments and comparative examples in the secondary battery are shown in Table 2.
[0178] Table 1 Performance test results of negative electrode materials prepared in various embodiments and comparative examples
[0179]
[0180] Table 2 Electrochemical performance results of the batteries prepared in each embodiment and comparative example
[0181]
[0182] also, Figure 1 The XRD spectrum of the negative electrode material prepared in Example 1 is also given, in which the MgSiO3 (610) diffraction peak appears between 30°-31°, and the Si (220) diffraction peak appears between 45°-50°.
[0183] Figure 2 and Figure 3 The SEM / EDS surface scanning image of the Mg element in a certain cross section of the negative electrode material prepared in Example 1 and the high-magnification SEM image of the cross section of the particle are respectively given. It can be seen from the figure that the metal silicate domain, the nano-silicon domain and the silicon oxide domain are uniformly dispersed with each other.
[0184] Figure 4 and Figure 5 The cycle-capacity diagram and the cycle-expansion diagram of the secondary battery prepared in Example 1 and Comparative Example 1 are respectively given. By comparison, it can be seen that the negative electrode material prepared in the present application has better cycle performance and lower cycle expansion performance.
[0185] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0186] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, any of the above-mentioned claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A negative electrode material, characterized in that: It comprises a silicon-based core and a carbon layer coated on the surface of the silicon-based core, wherein the silicon-based core comprises nano-silicon and a silicate containing a metal M element; The negative electrode material is subjected to cross-section and energy spectrum analysis, and the cross-sections of n1 particles are randomly selected for surface scanning analysis to obtain n1 M element content values, and the standard deviation k1 of the n1 M element content values is calculated, where k1≤10; n2 points are randomly selected inside the cross-section of the particle for point scanning analysis to obtain n2 M element content values, and the standard deviation k2 of the n2 M element content values is calculated, where k2≤5, and 0.1<k2 / k1≤1, wherein n1 is a natural number greater than or equal to 5, and n2 is a natural number greater than or equal to 5.
2. The negative electrode material according to claim 1, characterized in that At least one of the following conditions is met: (1) The silicon-based core also includes silicon oxide; (2) The pH value of the negative electrode material satisfies 7<pH≤10.5; (3) The M element includes at least one metal element from Groups IA, IIA, and IIIA; (4) The M element includes at least one of lithium, sodium, potassium, magnesium, calcium and aluminum; (5) The true density of the negative electrode material is 2.0 g / cm 3 -2.6g / cm 3 ; (6) The specific surface area of the negative electrode material is 2 m 2 / g-10m 2 / g; (7) In the negative electrode material, the mass proportion of the M element is 3%-20%, and the mass proportion of the carbon layer is 1%-20%; (8) When the silicate containing the metal M element includes MgSiO3, in the XRD spectrum of the negative electrode material, the diffraction peak of MgSiO3 (610) is between 30° and 31°, the diffraction peak of Si (220) is between 45° and 50°, and the ratio of the two diffraction peak intensities α=I Si(220) / I MgSiO3(610) , 0<α<2; (9) When the silicate containing the metal M element includes MgSiO3, according to the XRD spectrum of the negative electrode material and the Scherrer formula Kλ=0.9λ / Bcosθ, it is calculated that the average size of the MgSiO3 grains on the (610) crystal plane is ≤30nm.
3. The negative electrode material according to claim 2, characterized in that At least one of the following conditions is also met: (10) The nano-silicon is dispersed in the silicon oxide; (11) The nano-silicon or the silicon oxide is surrounded by the silicate containing the metal M element.
4. The negative electrode material according to any one of claims 1 to 3, characterized in that The thickness of the carbon layer is 50nm-500nm.
5. A method for preparing a negative electrode material according to any one of claims 1 to 4, characterized in that: include: Placing a metal source material and a pre-disproportionated silicon dioxide material at different positions in the same vacuum heating system for heating and evaporation respectively to obtain a metal source gas and silicon dioxide gas; Mixing and condensing the silicon dioxide gas and the metal source gas to obtain a core material; The core material is subjected to carbon coating treatment to obtain the negative electrode material.
6. The preparation method according to claim 5, characterized in that: At least one of the following conditions is met: A. The preparation method of the pre-disproportionated silicon oxide material comprises: pre-disproportionating an amorphous SiO block to obtain silicon oxide containing disproportionated silicon grains <10 nm, and then pulverizing or crushing to obtain the pre-disproportionated silicon oxide powder or particles; B. the size of the pre-disproportionated silicon dioxide material is ≤10 cm; C. The metal source material includes at least one of a magnesium source material, a lithium source material, a sodium source material, a potassium source material, a calcium source material, and an aluminum source material; D. the metal source gas comprises at least one of magnesium vapor, lithium vapor, sodium vapor, potassium vapor, calcium vapor, and aluminum vapor; E. The heating evaporation is carried out in a vacuum or inert gas atmosphere; F. The temperature at which the pre-disproportionated silicon dioxide material is heated and evaporated is 1000° C.-1500° C.; G. The temperature at which the metal source material is heated and evaporated is 600° C.-1350° C.; H. The condensation temperature is 500°C-800°C; I. The condensation method includes at least one of water cooling and air cooling; J. After the condensation, the method further comprises: collecting the precursor material after the condensation, crushing and classifying the precursor material to obtain the core material; K. The carbon coating treatment includes gas phase coating, liquid phase coating or solid phase coating.
7. The preparation method according to claim 6, characterized in that: At least one of the following conditions is met: L. The pre-disproportionation treatment is carried out in an inert gas atmosphere, wherein the inert gas comprises at least one of nitrogen, argon and helium; M. The temperature of the pre-disproportionation treatment is 1000°C-1200°C; N. The holding time of the pre-disproportionation treatment is 3h-10h; O. The magnesium source material includes at least one of metal magnesium powder, metal magnesium ingot, metal magnesium granules, a mixture of magnesium oxide and a reducing substance, and a mixture of magnesium salts and a reducing substance; P. The pulverizing method includes mechanical pulverizing, ball milling pulverizing or air flow pulverizing; Q. The gas phase-coated gas includes a carbon source gas and a carrier gas; R. The temperature of the gas phase coating is 700°C-1000°C.
8. The preparation method according to claim 7, characterized in that: At least one of the following conditions is met: S. The carbon source gas includes at least one of methane, ethane, propane, butane, ethylene, propylene, and acetylene; T. the carrier gas comprises at least one of nitrogen, argon and helium; U. The gas phase covering gas also includes hydrogen.
9. The preparation method according to any one of claims 5 to 8, characterized in that: The silicon dioxide gas and the metal source gas are mixed under a vacuum condition with a vacuum degree of 0-100 Pa.
10. A secondary battery, characterized in that: The negative electrode material comprises the negative electrode material according to any one of claims 1 to 4.
Citation Information
Patent Citations
Silicon-based negative electrode material, preparation method thereof and lithium ion secondary battery
CN111816859A
Silicon compound negative electrode material, preparation method thereof and lithium ion battery
CN112563476A
Lithium ion battery negative electrode material, preparation method and application
CN116779792A